Perancangan Sistem Informasi Penjualan Bunga Buket Berbasis Dekstop (Prodi Teknik Informatika (S1) Institut Teknologi dan Bisnis Indonesia, 2022)
Florist Barrel is a shop engaged in the sale of real flowers and fake flowers. Laras Florist is located on Jalan Melati Dusun I, Binjai District and has been established since 2016. This store still uses a manual system, where operational activities have not utilized existing computers. The storage media (Inventory) still uses paper, causing a buildup of documents. The processing of data and the creation of reports are slow so that in providing inventory information and reports takes a long time. So a system is needed that can process sales and stock in stores. The system was created using Microsoft Visual Studio 2010